Prevalencia de enfermedad diarreica aguda en las niñas y niños menores de cinco años atendidos en el centro de salud de el Pangui, cantón el Pangui, año 2015 - Orosco Salazar, Mirian Juliana (2016)
This research work was focus on determining the prevalence of acute diarrheal diseases in children under five years attended at the Health Center of the Pangui. The instruments applied were the survey and the direct observation by reviewing medical records of 158 children who conformed the sample. The methodology was cross-sectional, retrospective, descriptive, and bibliographic field type; whereas the prevalence of acute diarrheal disease was identified in a 21.56%, osmotic type 98% in the 53.80% male, mixed race ethnicity dominance with 91.14%, from urban 63.92% and the average economic level 100% with, being the main risk factor - intra-domiciliary presence of animals in an 83.90 %. -The early incorporation child supplementary feeding in a 76.58%. - 78.48% of children has not been fed breastfed - The 71.52% was by the consumption of untreated water. - 42.41% eat food like fruits without washing it. - 43.04% do not wash their hands frequently. - 78.48% were using feeding bottle. - 75.95%. For that reason, educational activities like; the development of an open house and leaflets, flyers also were given over. Prevalence of acute diarrheal disease is concluded in a 21.56% being a predisposing factor the early incorporation complementary feeding in children under one year old.